Association of High Density Lipoprotein with Platelet to Lymphocyte and Neutrophil to Lymphocyte Ratios in Coronary Artery Disease Patients. (13th November 2014) - Prajapati, Jayesh H.; Sahoo, Sibasis; Nikam, Tushar; Shah, Komal H.; Maheriya, Bhumika; Parmar, Meena
Abstract : Background . We aimed to evaluate a relationship between platelet-lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR) with high density lipoprotein (HDL) cholesterol levels in coronary artery disease (CAD) patients. Methods . A total of 354 patients with angiographically confirmed coronary blockages were enrolled in the study. Hematological indices and lipid profiling data of all the patients were collected. Results . We have observed significant association between HDL and PLR (P = 0.008 ) and NLR (P = 0.009 ); however no significant relationship was obtained with HDL and isolated platelet (P = 0.488 ), neutrophil (P = 0.407 ), and lymphocyte (P = 0.952 ) counts in CAD patients. The association was subjected to gender specific variation as in males PLR (P = 0.024 ) and NLR (P = 0.03 ) were highly elevated in low HDL patients, whereas in females the elevation could not reach the statistically significant level. The PLR (217.47 versus 190.3; P = 0.01 ) and NLR (6.33 versus 5.10; P = 0.01 ) were significantly higher among the patients with acute coronary syndrome. In young patients the PLR (P = 0.007 ) and NLR (P = 0.001 ) were inversely associated with HDL, whereas in older population only NLR (P = 0.05 ) had showed a significant association. Conclusion . We conclude that PLR and NLR are significantly elevated in CAD patients having low HDL levels.